2015
DOI: 10.4238/2015.march.20.16
|View full text |Cite
|
Sign up to set email alerts
|

Traditional risk factors and angiotensin-converting enzyme insertion/deletion gene polymorphism in coronary artery disease

Abstract: ABSTRACT. We investigated whether the insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene and serum ACE levels are associated with traditional risk factors of coronary artery disease (CAD). We enrolled 250 individuals without CAD and 750 individuals suffering from CAD who were angiographically diagnosed. Biochemical risk factors, the ACE (I/D) gene polymorphism, and ACE serum levels were compared. ACE genotypes were determined using real-time polymerase chain reaction. ACE ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Renin-angiotensin system genetic polymorphisms (I/D of ACE and AT1R ) were not associated with CAD severity in our study. However, the ACE gene was previously associated with higher ACE levels in D/D patients with CAD, 36 which was not confirmed in a larger sample.…”
Section: Discussionmentioning
confidence: 78%
“…Renin-angiotensin system genetic polymorphisms (I/D of ACE and AT1R ) were not associated with CAD severity in our study. However, the ACE gene was previously associated with higher ACE levels in D/D patients with CAD, 36 which was not confirmed in a larger sample.…”
Section: Discussionmentioning
confidence: 78%
“…Yang et al [ 54 ] reported that in Taiwanese individuals with AD, the DD genotype was related to increased levels of ACE in the plasma and that the I allele was associated with a decreased risk of AD; they thus characterized the D allele as a “risk” allele. Several studies linked the increased ACE concentrations with the DD genotype, CAD [ 55 ], hypertension [ 56 ], autoimmune diseases [ 57 , 58 ] and acute respiratory distress syndrome [ 59 ]. Moreover, Zhang et al [ 60 ] reported that the DD genotype was more frequent in patients with major adverse CV events among CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Cambien et al first reported positive association between D allele and myocardial infarction (MI). Since then, many scientists have investigated the ACE I/D polymorphism in relation to coronary artery disease and demonstrated positive association between D allele and CAD (Badenhop et al, 1995;Peterlin et al, 2000;Terzić et al, 2003;Acarturk et al, 2005;Istrati et al, 2006;Seckin et al, 2006;Freitas et al, 2008;Guney et al, 2013;Sahin et al, 2015). However, some other studies, conducted in different populations, did not establish strong correlation between the I/D polymorphism and CAD (Friedl et al, 1995;Agerholm-Larsen et al, 1997;Hernández et al, 2002;Oei et al, 2005;Kähönen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of the ACE I/D genotypes: DD (190bp, lane 1 and 6), ID (490/190bp, lane 2 and 4), II (490bp, lane 3, 5 and 7), DNA ladder (lane 8)2006;Freitas et al, 2008). Several studies in Turkish population(Acarturk et al, 2005;Seckin et al, 2006; Guney et al, 2013;Sahin et al, 2015) have also described the ACE I/D polymorphism as a risk factor for CAD. Research in Poland, reported byNiemiec et al (2007) suggested that the DD genotype/D allele increases the risk of CAD associated with the presence of traditional risk factors (smoking, hypercholesterolemia and obesity).…”
mentioning
confidence: 99%